Study of Using Paper Filter Whatman no.42 for Measuring Water Retention in Cement Paste - Dora Melati Nurita Sandi; Indarto Indarto; Ridho Bayuaji; Januarti Jaya Ekaputri (IPTEK The Journal for Technology and Science, 2016)
This paper is study about using paper filter Whatman no.42 for measuring water retention on cement paste. The research is conducted as experiment in laboratory by making two types of specimens. The first speciment is cement paste with variation of water cement ratio and the second one is foam cement paste. There are two step for measuring water retention on cement paste. The first step is specimen immersed with immersion duration (t1). The second step is searching of filter paper weight to obtain water content after contact with two specimen. t1is time of consistency water content on specimens. The parameters (t1) must be searched before measuring water retention. The result of measurement water retention be shown in a curve.